189k views
0 votes
How do I solve this?
-3x(x+14)

User SlimJim
by
4.2k points

2 Answers

3 votes
You first distribute the -3x to x so u have -3x^2 because you multiplied them. Then you do -3x times 14 which is -42. So the answer is -3x^2-42
User Jranalli
by
4.5k points
6 votes

Answer:


-3x^2-42x

Explanation:

Distributive property:

A(B+C)=AB+AC

A=-3x, B=x, and C=14

-3xx+(-3x)*14

(-b)+=-b

-3xx-3*14x

Simplify to find the answer.

-3xx-3*14x=-3x^2-42x


-3x^2-42x, which is our answer.

User LCZ
by
4.9k points